The Improving Student's Speaking Achievement By Using YouTube Media on New Normal Era - Endang Mastuti Rahayu; Mabruroh Mabruroh (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
This study aimed to demonstrate an improvement in speaking achievement among class X-1 ITP Surabaya students for the academic year 2022–2023. Their inadequate verbal communication abilities are the issue. As a result, the researcher used YouTube media during engaging class activities to teach speaking. Classroom action research is the approach used in this study. actions that are repeated twice. Both qualitative and quantitative analyses of the study's findings were performed. According to the findings, using YouTube media helped students' oral communication achievement, which was demonstrated by their exam scores. In cycle 1, 36% of students passed the exam; in cycle 2, that number rose to 84%. Student involvement increases and their activities take center stage during the learning process, according to observational findings. Additionally, the survey reveals that students strongly agree that using YouTube media during class activities makes them happy. This demonstrates how students' speaking achievement improved when using YouTube media for learning